Sustainable intensification of pineapple farming in Ghana: Training and complexity - David Wuepper; Johannes Sauer; Linda Kleemann (Kiel Institute for the World Economy (IfW), 2014)
Sustainable intensification of Ghana's smallholder farming is critical to mitigate rural poverty. Innovations for sustainable intensification include agro-ecological practices, which build up soil fertility, and mulching, which conserves soil moisture. To stimulate the adoption of these innovations, development organizations and business stakeholders provide training for farmers, to demonstrate proper usage and convince the farmers of their profitability. Using unique panel data, we analyze whether the provided training increases adoption-rates. We find effect of training is significant for the adoption of agro-ecological practices but not for mulching. The explanation is that agro-ecological practices are complex but inexpensive, so that information is the main constraint. Mulching in contrast is already a little more diffused, easier to understand but more expensive. Therefore, mulching is less constrained by lacking information and mostly by finance, which includes restricted credit access and uninsured risk.
Keywords: C3; C5; O2; O3; D8; Q1; 330; Agricultural Training; Sustainable Intensification; Development Organizations; Social Learning; Agro Ecological Practices; Mulching; Ghana